Strategy and medical approach to treatment of giant sacrococcygeal teratoblastoma with concomitant teratoma in a newborn child - V. S. Konoplitskyi; V. V. Pogorily; A. G. Dubrovin; O. A. Moravska; T. V. Chuhu; A. G. Yakymenko; O. A. Lukiyanets (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2018)
The work presents a clinical case of successful treatment of a giant sacrococcygeal teratoblastoma of external-internal localization and teratoma of internal localization in a newborn child. A preoperative preparation, surgery, and postoperative chemotherapy were administered to ensure a satisfactory result.